Combination of quadruple isotope dilution strategy and dispersive solid phase extraction method for accurate quantification of selected steroid hormones - Cagatay, Nese Ular; Bodur, Suleyman; Bodur, Sezin Erarpat; Mavis, Murat Emrah; Bakirdere, Sezgin (ROYAL SOC CHEMISTRY, 2025)
Steroid hormones are essential for the regulation of various vital body functions. Therefore, the determination of steroid hormones in biological fluids is a significant issue to find out the mechanism of steroid hormones related to disorders. In this study, Fe3O4/reduced graphene oxide (Fe3O4/rGO) nanocomposite based dispersive solid phase extraction (DSPE) was coupled with liquid chromatography - quadruple isotope dilution - triple quadrupole mass spectrometry (LC-ID4-MS/MS) for the accurate and precise determination of aldosterone, testosterone, 17-hydroxyprogesterone and estrone in serum samples. There is no study in literature about the combination of DSPE and LC-ID4-MS/MS methods for the extraction and determination of selected steroid hormones. Significant improvements in accuracy and precision for the proposed method was achieved by the combination of DSPE and LC-ID4-MS/MS. The percent recovery results were calculated between 100.0 and 103.4% with low percent relative standard deviation values (<= 2.0%). The obtained recovery results proved the application of the developed method with high accuracy and precision for the determination of steroid hormones in serum samples. Hence, the developed method is superior to the current analytical methods for the determination of selected steroid hormones in terms of sensitivity, accuracy and precision.
Keywords: LC-MS/MS ANALYSIS; MAGNETIC GRAPHENE OXIDE; MEASUREMENT UNCERTAINTY; ELEMENTAL SPECIATION; MASS-SPECTROMETRY; HUMAN SERUM; LIQUID; MICROEXTRACTION; VALIDATION; PRECISION; Chemistry; Food Science & Technology; Spectroscopy